The Effect of Profitability, Leverage, Sales Growth, Independent Commissioners, and Institutional Ownership on Tax Avoidance: Pengaruh Profitabilitas, Leverage, Sales Growth, Komisaris Independen, dan Kepemilikan Institusional terhadap Tax Avoidance - Agustiana, Sabila Dwi; Kusumawati, Eny (Procedia of Social Sciences and Humanities, 2022)
The still high cases of tax avoidance in Indonesia, prompting the need to identify the factors that affect tax avoidance. This study aims to determine and analyze the effect of profitability, leverage, sales growth, independent commissioners, and institutional ownership on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This research was designed using quantitative methods. The data used in this study were obtained from the website www.idx.co.id and the company's financial statements. The sampling technique used purposive sampling and obtained as many as 49 companies for each year. The total sample used is 245 and the data outlier is 41 so that the total sample is 204 during the 5-year observation period. The collected sample data was then tested for hypotheses using the method of multiple linear regression analysis, and statistical test analysis. The test results show that the profitability variable has a significant effect on tax avoidance. While the variables of leverage, sales growth, independent commissioners, and institutional ownership have no significant effect on tax avoidance.